Earnings momentum meets short‐term return reversal. (1st August 2020) - Zhu, Zhaobo; Sun, Licheng; Tu, Jun
Abstract: This paper evaluates the effectiveness of a joint strategy that exploits fundamental‐based momentum and return‐based reversal anomalies. This joint strategy is motivated by two considerations. First, reversal can serve as a natural hedge to momentum. Second, both fundamental and price‐related information can contribute to stock return predictability. Consequently, we propose a new joint strategy that synthesises both earnings momentum and short‐term reversal. We find that this joint strategy generates considerable economic gains and outperforms the sum of profits from two individual anomalies. Moreover, the proposed strategy appears to be quite robust, generating stable and persistent profits across different market conditions.